Tako-Tsubo Cardiomyopathy Due to Long-Term Hospital Stay: A Case Report - Cahide Uğur Erol; Mehmet Akif Yaşar; Alp Akay (Galenos Yayinevi, 2015)
Takotsubo cardiomyopathy (TC) is acute and temporal dysfunction of the left ventricle, and characterized by ballooning usually involving the apical region of the left ventricle without significant stenosis in coronary arteries. It is generally encountered after emotional or physical stress in women in the post-menopausal period. This left ventricular dysfunction recovers within days or weeks. Rarely, cardiogenic shock develops due to severe ventricular dysfunction, which may result in death. Although its pathophysiology is not fully understood, increased cathecolamines are considered to play an important role. Stunned myocardium, hypertension, chronic obstructive lung disease, decreased estrogen level, small vessel disease, myocarditis, insufficient metabolism of fatty acids of myocardium was also suggested. Sudden onset chest pain mimicking Acute coronary syndrome, dyspnea, syncope, ECG alterations, slight increase in myocardial enzymes may be detected. Frequently, such patients in coronary intensive care unit are transferred to general intensive care unit for respiratory support. To the best of our knowledge, there has been no TC syndrome in the literature, which develops in a patient under intensive stress due to an extraordinary long term hospitalization.